Cuckolding and Troilism: definitions, relational and clinical contexts, emotional and sexual aspects, and neurobiological profiles. A complete review and investigation into the borderline forms of the relationship: Open Couples, Polygamy, Polyamory - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2020)
Starting from the concept of "cuckold" and having placed the substantial differences with the "troilism", despite the terminological error committed by almost all the researchers who consider these two terms of synonyms, we proceeded to analyze the clinical, neurobiological and relational profiles, to then investigate the borderline forms of troilism: Open couples, polygamy and polyamory. By analyzing the possible etiological causes, which are the basis of these manifestations, it was concluded that probably the multifactorial is the most suitable answer, with a clear orientation towards the psychological causes deriving from a post-traumatic stress adaptation (substantially in the field of paraphilias or narcissism with adaptive forms, therefore self-destructive).